Patient Activation in Type 2 Diabetes: Does It Differ between Men and Women? - Steven H. Hendriks; Laura C. Hartog; Klaas H. Groenier; Angela H. E. M. Maas; Kornelis J. J. van Hateren; Nanne Kleefstra; Henk J. G. Bilo (Journal of Diabetes Research)
Background. Aim was to investigate whether the degree of patient activation of patients with type 2 diabetes (T2D) is different between men and women. Furthermore, we investigated which factors are associated with patient activation in men and women. Methods. This cross-sectional study included 1615 patients with T2D from general practices. Patient activation was measured with the Patient Activation Measure (PAM) questionnaire. Multivariate linear regression analyses were used to investigate the association between gender and patient activation. Stratified analyses according to gender were performed to investigate which factors are associated with patient activation. Results. No association between gender and PAM score was found after adjustment for all selected confounders (p=0.094). In men, lower age (p=0.001), a higher WHO-5 score (p<0.001), and a lower BMI (p=0.013) were associated with a higher PAM score. In women, a higher WHO-5 score (p<0.017) and the absence of macrovascular complications (p<0.031) were associated with a higher PAM score. Conclusion. There is no difference in the degree of patient activation of men and women with T2D. Age, well-being, and BMI were found to be associated with patient activation in men, whereas well-being and macrovascular complications were found to be associated with patient activation in women.